Infantile Systemic Hyalinosis Complicated with Right Atrial Thrombus and Pericardial Effusion in an Infant - Sarar Mohamed; Wafa Ahmed; Nasir Al-Jurayyan; Eisa Faqeih; Abdulrahman Al-Nemri; Mohamed Al-Ghamdi (Elsevier, 2017)
Infantile systemic hyalinosis (ISH) is a rare multisystem fatal autosomal recessive disorder that involves widespread deposition of hyaline on connective tissues and certain internal organs. The major manifestations include painful articular contractures, hyperpigmentation, subcutaneous nodules, gingival hypertrophy, failure to thrive secondary to protein-losing enteropathy, and osteolytic bone lesions. In this paper, we report a 12-month-old girl with ISH presenting with recurrent diarrhea, failure to thrive, and refractory infections. A molecular study identified a homozygous missense mutation, c.134T > C; p.L45P, in exon 1 of the anthrax toxin receptor 2 (ANTRX2) gene. Our patient passed through an eventful course that included septic shock, central line infections, right atrial thrombosis, and pericardial effusion. She incurred acute bronchiolitis due to respiratory syncytial virus infection, which led to her death. In conclusion, this case report highlights that severe and life-threatening morbidities and complications can be encountered in ISH, to which some management options can be applied.